Gender differences and culture in english short message service language among malay university students - Yuen, Chee Keong; Saran Kaur Gill; Maisarah Noorezam; Asma’a Abdulrazaq (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2012)
This paper examined the sociolinguistic aspect of Short Message Service (SMS) language, particularly in identifying gender differences and in revealing how Malay culture could be represented in SMS texts. The research applied both qualitative and quantitative approaches on 20 Malay postgraduate students of Universiti Kebangsaan Malaysia: 10 male texters and 10 female texters aged between 24-30 years old. Data collection involved 40 SMSes; 20 text messages from each gender and interviews with four participants. The predetermined categories namely abbreviation, emotion, onomatopoeic and word length were selected to fulfill the aims and scope of the study. Hence, Shafie et al (2011) and Balakrishnan & Batat’s (2010) framework of abbreviation, emotion and onomatopoeic, and word length was used. Based on the analysis, it was revealed that there were no gender differences in the use of abbreviations. However, females showed more use of emotions, onomatopoeic and their text messages were longer than males. These findings were confirmed by all the interviewees. The findings also revealed some culture aspects; both the Malay word “lah” and the translation of Malay proverbs into English which are used among Malays in their language were detected.